Strengthening Digital Literacy and Organizational Management System Based on ISO 21001 to Support Kurikulum Merdeka: Penguatan Literasi Digital dan Sistem Manajemen Organisasi Berbasiskan ISO 21001 untuk Mendukung Kurikulum Merdeka - Yunis, Roni; Sudarto, Sudarto; Ginting, Sugianta Ovinus; Jeni, Mutiara; Riri, Riri; Wijaya, Viona Guanita (Universitas Lancang Kuning, 2025)
The community service (PkM) aims to improve digital literacy and ISO 21001 implementation at SMAN 2 Lubuk Pakam to support the Kurikulum Merdeka. The methods used include socialization, training, technology application, mentoring, and evaluation. The results showed an increase in digital literacy understanding by 2.20% and ISO 21001 implementation by 5.70%, with participant participation in activities reaching 94.60%. In addition, the program also produced a community of digital creators and an internal quality assurance unit that is expected to play an active role in improving the quality of education. The application of technology and ISO 21001 has proven to play an important role in supporting information technology-based learning, especially through the Learning Management System (LMS). The sustainability of this program is expected to strengthen the capacity of SMAN 2 Lubuk Pakam in facing the challenges of education in the digital era, as well as improving the quality of learning